An Oral Sedation Preparation Based on Pistachio Nuts with Organic Melatonin Content To Support MRI Examination - Surya Wrddhi Putra, IM Dwitya; Satoto, Bambang; Dartini, Dartini; Masrochah, Siti; Latifah, Leny; Murti Wibowo, Gatot (Pelopor Publikasi Akademika, 2024)
Sedation of propofol, chloral hydrate, midazolam, and ketamine is commonly used in MRI examinations. There are still risky side effects from the previous 4 sedations, so melatonin tablets are a safer option. Melatonin synthesized in tablets can still cause quite adverse side effects. Pistachios processed into milk can be used as an alternative to natural melatonin oral sedation. Research Objective: To determine the potential of pistachio milk as an alternative to oral melatonin sedation to support MRI examinations. Research Method: This research uses the R&D (Research and Development) method with 4 stages, namely finding potentials and problems, data collection, product design, and design validation. The product in the form of 200 mL pistachio milk with concentration variants of 35 g, 45 g, 55 g, 65 g was tested in a laboratory to determine its potential from the test results with a reference to melatonin tablets of 10 mg. Research Results: Laboratory tests showed the presence of melatonin and other accompanying ingredients such as phenolics, carotene, and polyphenols. The melatonin content of the 35 g, 45 g, 55 g, 65 g variants is 5.5 mg, 6.1 mg, 8.7 mg, 10.5 mg, respectively. Conclusion: Pistachio milk with a 65 g variant has a melatonin content of 10.5 mg which is close to the reference for sedation of melatonin tablets of 10 mg, so it has the potential to be an alternative to oral sedation of melatonin to support MRI examinations.